Enhancing the Mechanical Properties of Soil using Orange Peel Ash: Modeling and Experiments - AbdulRahman, Sh.Muthana; Al-Soudani, Maha; Salman Dawood Salman AL-Dulaimi; Svetlov Dmitry Anatolyevich (Journal of Engineering and Sustainable Development, 2025)
Using agricultural waste products as sustainable resources significantly contributes to the country's development. This research aims to assess the efficacy of mixing soil with orange peel ash by employing Atterberg limits, unconfined compressive strength, and collapse as evaluation parameters. Four models were developed to measure the cumulative failure loads both before and after soil treatment using a combination of 9% orange peel and 3% cement ash. The experimental tests will be undertaken at 7, 14, and 28 days. Moreover, two mathematical equations were derived to demonstrate the correlation between the liquidity index, soil-bearing capacity, and cohesion. The models revealed that the foundation's bearing capacity on saturated clay soil increased from 49 KPa without treatment to 115, 275, and 460 KPa at 7, 14, and 28 days of drying. Mixing 9% orange peel ash with 3% cement improves soil properties and reduces the percentage of cement. To evaluate the effectiveness of soil, it is necessary to apply orange peel ash to the area that lacks nutrients. Ash has properties that decrease soil reactivity, increase cohesiveness, and strengthen the soil's resistance to external stresses. Through the implementation of sustainable waste recycling, the productivity of low-quality clay soil can be improved.